Peran Motivasi Kerja Dalam Meningkatkan Produktivitas Kayawan Pada Wirman Sambel - Muh Nur Khalish; Andi Indriani Ibrahim; Harnida Wahyuni Adda; Suryadi Samudra (Jurnal Publikasi Sistem Informasi dan Manajemen Bisnis, 2024)
This study was conducted to determine how work motivation is carried out by wirman sambel and how the productivity of wirman sambel employees in the application of work motivation. This research is presented with descriptive qualitative method, the author thoroughly observes the work motivation of WIRMAN SAMBEL employees in increasing work productivity. The result of this study is that work motivation has a relationship with work productivity, which work productivity is highly dependent on work motivation. The application of work motivation to wirman sambel employees is in the form of: communication, appreciation, sense of responsibility, and cooperation. So that productivity can be formed.